Analysis of DNA from fingernail samples in criminal cases. (December 2015) - Bozzo, W.R.; Colussi, A.G.; Ortíz, M.I.; Laborde, L.; Pilili, J.P.; Carini, G.; Lojo, M.M.
Abstract: The detection of foreign DNA from the fingernail hyponychium may be relevant in the investigation of certain criminal acts, providing evidence of any sort of contact between the victim and the suspect. In this report, we analyzed results obtained from 164 fingernail samples collected by three different methods: extraction, clipping and swabbing. Samples were taken, mostly during the autopsy operation, and submitted to our Lab in the context of 71 different criminal cases. In 74.6% of the reviewed cases, a reportable DNA profile which matched the victims was recovered. In 13.2% of these profiles, foreign DNA was also detected as a minor contributor, representing almost a 10% of the analyzed cases. The estimated prevalence of foreign DNA samples beneath fingernails is comparable with that reported from volunteer donors screenings.